Effectiveness of a 4% Emprit Ginger Gel in Reducing Pain Intensity and Salivary Cortisol Levels Among Adolescents with Primary Dysmenorrhea: A Randomized Controlled Trial on Topical Therapy for Primary Dysmenorrhea - Windi Mei Safitri; Suharyo Hadisaputro; Sri Sumarni (Poltekkes Kemenkes Yogyakarta, 2026)
Dysmenorrhea is highly prevalent among Indonesian adolescents in Indonesia and adversely affects pain perception, concentration, daily functioning, and quality of life. This study aimed to develop a stable and standardized 4% emprit ginger gel, a topical formulation designed to enhance penetration and ease of use, and to evaluate its effectiveness in reducing pain intensity and modifying salivary cortisol levels in adolescents with primary dysmenorrhea. This study employed a randomized controlled true experimental design was conducted at a senior high school in Surakarta, Indonesia, between June and July 2025. Inclusion criteria included female students experiencing primary dysmenorrhea for the previous three menstrual cycles, who had never married or given birth, not using other complementary therapies, and willing to participate. Thirty-six eligible adolescents were randomly assigned to the intervention group (4% ginger gel, 2 grams) or the control group (cajeput oil, 2 ml) using a lottery system. Both interventions were applied twice daily for three consecutive days during menstruation. Pain intensity was measured using Numeric Rating Scale (NRS), and salivary cortisol levels was measured using enzyme-linked immunosorbent assay (ELISA) on the first and third days. Compared with cajeput oil, the 4% emprit ginger gel produced significantly greater reduction in pain intensity. Meanpain reduction was greater in the intervention group (3.67±0.97, p=0.017). Mean cortisol reduction also was greater in the intervention group 4.972±6.65, p=0.043). The findings support the use of 4% emprit ginger gel safe and effective complementary therapy adolescents with primary dysmenorrhea